The lonely crowd : a study of the changing American character - Riesman, David, 1909-2002; Denney, Reuel, 1913-1995; Glazer, Nathan, 1923-2019 (Garden City (N.Y.) : Doubleday, 1954)
"One of the most important books of the twentieth century."--Gideon Lewis-Kraus, New Yorker Considered by many to be one of the most influential books of the twentieth century, The Lonely Crowd opened exciting new dimensions in our understanding of the problems confronting the individual in twentieth-century America. Richard Sennett's new introduction illuminates the ways in which Riesman's analysis of a middle class obsessed with how others lived still resonates in the age of social media. "Indispensable reading for anyone who wishes to understand American society. After half a century, this book has lost none of its capacity to make sense of how we live."--Todd Gitlin